A Call to the CMS: Mandate Adequate Professional Nurse Staffing in Nursing Homes. Issue 3 (March 2021) - Kolanowski, Ann; Cortes, Tara A.; Mueller, Christine; Bowers, Barbara; Boltz, Marie; Bakerjian, Deb; Harrington, Charlene; Popejoy, Lori; Vogelsmeier, Amy; Wallhagen, Margaret; Fick, Donna; Batchelor, Melissa; et al.
Abstract : Editor's note: This article is by 22 nursing gerontology experts who are all advocates of nursing home reform. They are listed at the end of this article. Abstract : The authors address the association between low RN staffing levels and poor health outcomes in nursing homes and urge the Centers for Medicare and Medicaid Services (CMS) to enact reform.